2017
DOI: 10.1080/07373937.2016.1256890
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of atmospheric freeze-dried apples as affected by ultrasound application and sample surface

Abstract: Atmospheric Freeze Drying (AFD) yields products of a similar quality to the conventional vacuum freeze drying technique, but reduces the operating cost. However, it involves very low drying rates. The sample surface/mass ratio is one of the process variables that can be taken into account to reduce drying time. Moreover, power ultrasound (US) can also be used to intensify this process because of its effects on external and internal mass transfer resistance. However, both factors may affect not only the drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…For TPC, the degradation in samples dried without ultrasound 343 application was 48.9%, while it was 66.2% at 25 W and 66.0% at 50 W. In the case of 344 AC, the influence was more important, moving from 20.6% in the experiments without 345 ultrasound to 59.2% and 52.7% at 25 W and 50 W respectively. Other authors found a 346 similar effect of ultrasound application during low-temperature drying in the antioxidant 347 properties of products (Moreno et al, 2017;Santacatalina et al 2014;2016a). In general, 348 the effects produced by ultrasound on product structure could promote other oxidation 349 reactions that affect the antioxidant potential of samples.…”
Section: 3influence Of the Ultrasonic Power Applied On The Antioximentioning
confidence: 79%
“…For TPC, the degradation in samples dried without ultrasound 343 application was 48.9%, while it was 66.2% at 25 W and 66.0% at 50 W. In the case of 344 AC, the influence was more important, moving from 20.6% in the experiments without 345 ultrasound to 59.2% and 52.7% at 25 W and 50 W respectively. Other authors found a 346 similar effect of ultrasound application during low-temperature drying in the antioxidant 347 properties of products (Moreno et al, 2017;Santacatalina et al 2014;2016a). In general, 348 the effects produced by ultrasound on product structure could promote other oxidation 349 reactions that affect the antioxidant potential of samples.…”
Section: 3influence Of the Ultrasonic Power Applied On The Antioximentioning
confidence: 79%
“…It seems that ultrasound application leads to a better retention of AA in these cases, as was mentioned with regard to bioactive compounds. This better retention of AA was probably due to the shortening of the drying time, which reduces the thermal exposure of the samples and, consequently, the antioxidant activity degradation; or it might be related to a response mechanism of the tissue activated by ultrasound as reported by Moreno et al 37 These results therefore correlated better with the retention of bioactive compounds mentioned above when ultrasound was applied at 15 ∘ C. In hot air, significantly higher (P < 0.05) AA (FRAP method) was observed in passion fruit peel dried at 40 and 50 ∘ C and 1 m s −1 with ultrasound application (at 30.8 kW m −3 ) than without ultrasound application. 26…”
Section: Antioxidant Activitymentioning
confidence: 71%
“…It seems that ultrasound application led to a better retention of TPC in these cases, probably due to the shortening of the drying time, which reduces the thermal exposure of the samples and, consequently, the bioactive compound degradation. According to Moreno et al, 37 the application of ultrasound can activate a response mechanism in the tissue that induces the formation of new phenolic compounds, not only through the combination of existing compounds but also via the activation of secondary metabolic pathways. Furthermore, the fact that the ultrasonic treatment produced a possible inactivation of oxidative enzymes must also be considered.…”
Section: Bioactive Compounds Determinationsmentioning
confidence: 99%
“…[2,8]. In fact, the influence about drying process on antioxidant activity of apples and been previously studied not ontly in apple flesh [9,10,11] but also in apple skin. [2] Taking into account the final quality of the product, the drying processes at low temperatures emerges as an excellent alternative.…”
Section: Introductionmentioning
confidence: 99%